Islamic Education as A Solution for the Moral Decadence Problems - Amanah, Siti (International Conference of Moslem Society, 2019)
Moral decadence or moral deterioration is one of the problems that still exist in Indonesia. Students also cannot be separated from the spotlight on moral decadence.Brawls, bullying, disrespect for teachers are a few examples of moral decadence among students. Parents and teachers are looking for solutions to solve this problem, whether parents can solve it, or only the school can solve it, or there must be collaboration between parents and the school to solve this problem, or are there other factors can support the resolution of this problem. The purpose of this study is to show the efforts of Islamic education in providing solutions to problems of moral decadence or moral deterioration that occur, especially among students. This research method uses the method of literature, which examines the theory and looks at the cases published in the news about moral decadence, especially in students. The results of this study are that Islamic education is very influential on moral formation, because man's main function is as a caliph and to worship and serve him must surely have good knowledge, insight, behavior or morals, and so on. Someone who first gets an education including moral education is from both. If his family bases Islamic education as the foundation for the moral formation of children, then he will understand which behaviors are good and which are bad behaviors, manners, and so on.